Crime Science An Interdisciplinary Journal - Bowers, Kate.; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Crime Science is an international, interdisciplinary, peer-reviewed journal with an applied orientation. The journal's main focuses are on research articles and systematic reviews that reflect the growing cooperation among a variety of fields, including environmental criminology, economics, engineering, geography, public health, psychology, statistics and urban planning, on improving the detection, prevention and understanding of crime and disorder. Crime Science will publish theoretical articles that are relevant to the field, for example, approaches that integrate theories from different disciplines. The goal of the journal is to broaden the scientific base for the understanding, analysis and control of crime and disorder. It is aimed at researchers, practitioners, and policymakers with an interest in crime reduction. It will also publish short contributions on timely topics including crime patterns, technological advances for detection and prevention, and analytical techniques, and on the crime reduction applications of research from a wide range of fields. Crime Science publishes research articles, systematic reviews, short contributions and theoretical articles. While Crime Science uses the APA reference style, the journal welcomes submissions using alternative reference styles on a case-by-case basis. If you would like to submit an article in a different reference style, please contact editorial@crimesciencejournal.com for consideration.
Keywords: Criminology; Data protection; Community psychology; Signal processing; Criminology; Data and Information Security; Community Psychology; Signal, Speech and Image Processing